Regulation of spermatozoa motility in response to cations in Russian sturgeon Acipenser gueldenstaedtii - Li, Ping; Li, Zhi-Hua; Hulak, M; Rodina, M; Linhart, O (Theriogenology, 2012)
The aim of this study was to investigate the response of Russian sturgeon (Acipenser gueldenstaedtii) sperm to external cations (Na(+), K(+), Ca(2+), and Mg(2+)) and their susceptibility on the induction of motility and swimming behavior. An in vitro spermatozoa motility assay was used by a computer-aided Motion-Analysis system. Sperm motility was inhibited by 60 mM NaCl (~140 mOsm/kg) and 0.7 mM KCl solutions (~ 21.4 mOsm/kg). The Ca(2+) and Mg(2+) ions were not able to inhibit spermatozoa motility. By contrast, Na(+) within a limited concentration range (between 45 and 55 mm) was able to reverse the inhibitory effect of K(+) at the critical concentration (0.7 mM). Ca(2+) and Mg(2+) were also able to reverse the K(+)-mediated spermatozoa motility restriction at concentrations starting at 0.01 and 0.1 mM, respectively. These results provide evidence for the role of K(+) in suppressing spermatozoa motility, and suggest that Ca(2+), Mg(2+), and possibly Na(+) trigger motility in Russian sturgeon sperm.
Keywords: draslík; Fishes; osmolární koncentrace; plavání; Osmolar Concentration; ryby; Calcium; kationty; vztah mezi dávkou a účinkem léčiva; Spermatozoa; hořčík; Swimming; Dose-Response Relationship, Drug; vodní hospodářství; analýza spermatu; Sperm Motility; motilita spermií; Sodium; Aquaculture; vápník; mužské pohlaví; spermie; sodík; Potassium; Semen Analysis; zvířata; Cations; Animals; Male; Magnesium